EVALUASI KEBUTUHAN DAN KETERSEDIAAN AIR IRIGASI DALAM RANGKA PENINGKATAN HASIL PERTANIAN : (Studi Kasus: Daerah Irigasi Cikunten II) - Komala Sari, Novia (Menara: Jurnal Teknik Sipil, 2023)
The availability of water in irrigation areas can affect agricultural productivity. Water balance must be maintained so that there is no shortage of water. Cikunten II has an area of 4.362 ha, mostly in the Tasikmalaya district. This study aims to analyze the water requirement and balance. Data analysis used the KP01 guidelines and the Cropwat program. The data analysis results obtained differences in reference plants' evapotranspiration results using the Modified Penman method in KP and Pennman–Monteith in the Cropwat program. The difference between the two methods is 133,83% due to the difference in albedo coefficients. The effective rainfall for paddy and secondary crops, the KP method analysis is lower than the Cropwat simulation of 110.10%. Availability of water using data from the Ciwulan weir with a reliability of 80% obtained a maximum discharge of 2,73 m3/sec. The water requirement was calculated during planting periods I, II, and II. The KP method is greater than the Cropwat method with a percentage of 277.42% in analyzing water requirements in the Paddy-Paddy-plants cropping pattern. The availability of water in the Cikunten area using Cropwat has fulfilled the needs marked by a more stable k factor than the KP01 method.